Cinta Merek Sebagai Mediasi Antara Kepercayaan Merek, Gairah Merek Dan Niat Beli Kembali - Kadarusman Kadarusman; Evi Maria; Dwi Danesty Deccasari (JURNAL ILMIAH MANAJEMEN & BISNIS, 2019)
The purpose of this study was to examine the effect of brand passion, brand trust on repurchase intention and brand love as a mediating variable. Brand passion, brand trust and brand love directly have a significant and positive effect on repurchase intention. Brand love is a variable that mediates the influence between brand passion and repurchase intention, with the nature of mediation is full mediation.Brand love is also a variable that mediates the influence between brand trust and repurchase intention with the full mediation nature of mediation. Increased passion and trust in the brand will increase the love for the brand which will ultimately make consumers make purchases.